2015
DOI: 10.1007/s00394-015-1056-1
|View full text |Cite
|
Sign up to set email alerts
|

Daily intake of fermented milk with Lactobacillus casei strain Shirota reduces the incidence and duration of upper respiratory tract infections in healthy middle-aged office workers

Abstract: PurposeAlthough several studies have demonstrated the efficacy of probiotics for preventing upper respiratory tract infections (URTIs) in at-risk populations, including children and the elderly, few studies have investigated the efficacy of probiotics in healthy adults living normal, everyday lives. Thus, we tried to evaluate the effects of Lactobacillus casei strain Shirota-fermented milk (LcS-FM) on the incidence of URTIs in healthy middle-aged office workers.MethodsIn a randomized controlled trial, 96 eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 37 publications
2
129
0
2
Order By: Relevance
“…Our findings have significance for immunosurveillance; for example, NK cells are important in physiological immune surveillance, for example lysis of virally infected cells and tumour cells, and low human NK cell activity has been linked to an increased cancer risk . Furthermore, human studies indicate an association between LcS ingestion and protection against various cancers and upper respiratory tract infections .…”
Section: Discussionmentioning
confidence: 69%
“…Our findings have significance for immunosurveillance; for example, NK cells are important in physiological immune surveillance, for example lysis of virally infected cells and tumour cells, and low human NK cell activity has been linked to an increased cancer risk . Furthermore, human studies indicate an association between LcS ingestion and protection against various cancers and upper respiratory tract infections .…”
Section: Discussionmentioning
confidence: 69%
“…Gleeson et al reported that reduced levels of salivary IgA are associated with increased frequency of URTIs. As people age, they experience a decline in their immune responses; in turn, as the immune defence activities are relatively weak in such populations, they generally experience more infections . In addition, URTI outbreaks easily spread in nursing homes, and elderly people living in nursing homes are hence especially prone to URTIs.…”
Section: Discussionmentioning
confidence: 99%
“…19 billion in 2015 and it is projected to reach USD46.55 billion by 2020; dominated by Asia-Pacific market [11]. The applications of probiotics as alternative biotherapeutics have been successfully demonstrated in treatment of respiratory infection [12], inflammatory bowel disease [13], antibiotic associated diarrhoea [14] and ulcerative colitis [15]. In spite of the booming in vitro and in vivo probiotic studies against metabolic diseases such as T2DM, their application at clinical settings remains scarce [16,17].…”
Section: Introductionmentioning
confidence: 99%